Selection of Bacillus thuringiensis for control of root-knot nematodes on tomato - Pham, Thi My; Le, Thi Mai; Xuan, Dong Bui (Hue University Journal of Science: Natural Science, 2025)
Root-knot nematodes (Meloidogyne spp.) are among the most serious pests, reducing the yield and quality of tomatoes (Solanum lycopersicum) in Vietnam. Prolonged use of chemical pesticides has led to numerous negative impacts on the environment and human health. This study was conducted to select native Bacillus thuringiensis strains capable of controlling Meloidogyne spp. From soil samples collected from tomato fields in Danang, we isolated seven Bacillus strains, of which two strains, M2 and M5, were capable of producing toxic crystals. Strain M5 exhibited the highest inhibitory activity against Meloidogyne spp. J2 larvae in in vitro tests, achieving a mortality rate of 86.67% after 12 hours. Strain M5 was capable of producing key extracellular enzymes, including chitinase, protease, and cellulase. Sequencing of the 16S rRNA gene confirmed that strain M5 belongs to the species Bacillus thuringiensis (99.86% similarity with Bacillus thuringiensis MK743981.1). At a concentration of 10⁹ CFU/ml, strain M5 caused 100% mortality of J2 larvae after 10 hours and inhibited 88.9% of egg hatching. In greenhouse conditions, treatment with strain M5 significantly reduced the number of root galls on tomato plants (14.93 galls/plant) compared to the infected control (35.84 galls/plant). These results indicate that B. thuringiensis strain M5 is a promising biological control agent for managing root-knot nematodes on tomatoes. <!–a=1–>